PENGALAMAN SUAMI TERHADAP AKTIVITAS SEKSUAL PADA ISTRI MENOPASE DI KELURAHAN PONDOK AREN TANGERANG SELATAN - Nurhikmah Fujianty (STIKes IMC Bintaro, 2017)
Sexuality after menopause women experienced various changes one of them related to the fulfillment of sexual needs.This study aims to know about changes in activity sexual husband on menopause wife. This research uses qualitative method of descriptive phenomology with in-depth interview method. Participants include husband and wife who have menopause with menopause time up to three years obtained through purposive sampling. Data collected in the form of recording interviews and field notes were analyzed by applying Collaizi technique. The results of this study identified three themes namely : 1) Sexual intercourse consists of seeking satisfaction. 2) Changes in activity cycles consisting of dyspraenia, decreased frequency,decreased duration, satisfied and dissatisfied. 3) Happines and great sexsuatily and family. Suggested to health officers especially regarding sexual health and reproductive health of married couples.